(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2014)
The antimicrobial effect of white vinegar and lemon was evaluated for the control of Staphylococcus aureus in fresh salads prepared in the restaurants of the School Feeding Program (PAE) of San José de Cúcuta. A strain of Staphylococcus aureus was identified from fresh salads prepared in the restaurants of the school feeding program (PAE), applying NTC 4779 (horizontal method for the enumeration of coagulase-positive Staphylococcus). After this, the white vinegar and lemon were titrated against the microorganism under study at different concentrations (25 ppm, 50 ppm, 75 ppm, 100 ppm, 200 ppm and 500 ppm) using the echometric technique and the minimum inhibitory concentration. Furthermore, the additive with the greatest effect was determined by applying the diffusion antibiogram technique. The results obtained in the minimum inhibitory concentration test show that both white vinegar and lemon reduced the concentration of S. aureus without dilution, and that the additive that presented the greatest inhibition on this microorganism was lemon, which in the diffusion antibiogram, showed a halo of 30 mm. As a result, it was found that lemon reduces the microbial load, especially of Staphylococcus aureus, and also helps maintain the organoleptic properties of vegetables.